2018
DOI: 10.1016/j.ydbio.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Disparate levels of beta-catenin activity determine nephron progenitor cell fate

Abstract: Formation of a functional kidney depends on the balance between renewal and differentiation of nephron progenitors. Failure to sustain this balance can lead to kidney failure or stem cell tumors. For nearly 60 years, we have known that signals from an epithelial structure known as the ureteric bud were essential for maintaining this balance. More recently it was discovered that one molecule, Wnt9b, was necessary for both renewal and differentiation of the nephron progenitor cells. How one ligand signaling thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…By contrast, Six2:Cre and Wt1:CreER T2 induced deletions did not interfere with stromal Rspo3 expression, which bestowed sufficient b-catenin signalling in progenitors to permit survival. This hypothesis is compatible with a model in which low and high levels of b-catenin signalling regulates Class II and Class I target genes, respectively 10 . However, the concept of lower b-catenin signalling in uncommitted progenitors seems contradictory considering that they are exposed to higher levels of Rspondins (RSPO1+RSPO3), when compared to cells that engage in MET (only RSPO1).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…By contrast, Six2:Cre and Wt1:CreER T2 induced deletions did not interfere with stromal Rspo3 expression, which bestowed sufficient b-catenin signalling in progenitors to permit survival. This hypothesis is compatible with a model in which low and high levels of b-catenin signalling regulates Class II and Class I target genes, respectively 10 . However, the concept of lower b-catenin signalling in uncommitted progenitors seems contradictory considering that they are exposed to higher levels of Rspondins (RSPO1+RSPO3), when compared to cells that engage in MET (only RSPO1).…”
Section: Discussionsupporting
confidence: 87%
“…Class I genes such as Wnt4 that depend on strong b-catenin activation and are highly expressed in pretubular aggregates 5,10 . In situ hybridisation (Ish) analysis revealed that loss of R-spondins did not impact Wnt9b expression ( Fig.…”
Section: Rspo1 and Rspo3 Are Required For Mesenchyme-to-epithelial Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, work in cells derived from E10.5 mesonephric mesenchyme identified a role for Rspo1, Lrp6 and Fzd5 in enabling Wnt9b responsiveness as cells transitioned from the intermediate mesoderm to the metanephric mesenchyme identity (Dickinson et al, 2019). It was further demonstrated that low signaling input promotes selfrenewal and high signaling input promotes differentiation (Ramalingam et al, 2018). Our findings explain how Wnt9b signal strength varies to control both decisions, changing over time: a cell intrinsic and progressive increase in translation leads to increased stability (more Rspo, Lrp, Lgr proteins) and clustering (via Tmem59) of Wnt/FZD complexes.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Studies in mice have shown that Osr1, Six2, Wnt and Wt1 are required to maintain renal progenitor cells during kidney organogenesis. 6,7,8,9,10,11 Additionally, signalling pathways such as Wnt, Fgf, Tgfβ and Notch play major roles in renal stem cell maintenance and differentiation. 12,13,14,15 The transcription factor, Odd-skipped related 1 (Osr1), is an early marker specific for the intermediate mesenchyme (IM); knockout mice lack renal structures due to the failure to form the IM.…”
Section: Introductionmentioning
confidence: 99%